2010
DOI: 10.1152/japplphysiol.00515.2010
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular-mediated increase in central serotonin plays an important role in hypergravity-induced hypophagia in rats

Abstract: Exposure to a hypergravity environment induces acute transient hypophagia, which is partially restored by a vestibular lesion (VL), suggesting that the vestibular system is involved in the afferent pathway of hypergravity-induced hypophagia. When rats were placed in a 3-G environment for 14 days, Fos-containing cells increased in the paraventricular hypothalamic nucleus, the central nucleus of the amygdala, the medial vestibular nucleus, the raphe nucleus, the nucleus of the solitary tract, and the area postre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 32 publications
5
38
0
Order By: Relevance
“…We showed previously that hypergravity elevates 5-HT concentration in the cerebrospinal fluid, which is completely abolished by the vestibular lesion [34]. In addition, intensive interactions between 5-HT and BDNF in the brain were reported [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed previously that hypergravity elevates 5-HT concentration in the cerebrospinal fluid, which is completely abolished by the vestibular lesion [34]. In addition, intensive interactions between 5-HT and BDNF in the brain were reported [35].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that hypergravity increases 5-HT concentration in rodent cerebrospinal fluid [34]. 5-HTRs are widely distributed in the brain, and animal experiments using gene-knockout techniques and pharmacological experiments using receptor agonists/antagonists have reported that multiple 5-HTRs such as 5-HT1AR, 5-HT1BR and 5-HT2AR are involved differentially in emotion and cognition [20,4043].…”
Section: Discussionmentioning
confidence: 99%
“…A 3 g environment was induced by centrifugation, and the cages (30 cm × 18 cm × 14 cm) were set in a custom‐made gondola‐type rotating box with a 1.5 m arm (Shimadzu, Kyoto, Japan) for 4 weeks as described previously (Abe et al. ). To obtain 3 g environment, 41 rpm was applied.…”
Section: Methodsmentioning
confidence: 99%
“…“Vestibular-mediated increase in central serotonin plays an important role in hyper gravity-induced hypophagia in rats” (Abe et al, 2010). …”
Section: Pump Advantages Anonymous (2011ab) Over Other Selected Methmentioning
confidence: 99%